Formation and Reactivity of a Hexahydridosilicate [SiH6]2− Coordinated by a Macrocycle‐Supported Strontium Cation. Issue 10 (14th January 2022) - Höllerhage, Thomas; Ghana, Priyabrata; Spaniol, Thomas P.; Carpentier, Ambre; Maron, Laurent; Englert, Ulli; Okuda, Jun
Abstract: The cationic benzyl complex [(Me4 TACD)Sr(CH2 Ph)][A] (Me4 TACD=1, 4, 7, 10‐tetramethyltetraazacyclododecane; A=B(C6 H3 ‐3, 5‐Me2 )4 ) reacted with two equivalents of phenylsilane to give the bridging hexahydridosilicate complex [(Me4 TACD)2 Sr2 (thf)4 (μ‐κ 3 : κ 3 ‐SiH6 )][A]2 (3 a ). Rapid phenyl exchange between phenylsilane molecules is assumed to generate monosilane SiH4 that is trapped by two strontium hydride cations [(Me4 TACD)SrH(thf) x ] + . Complex 3 a decomposed in THF at room temperature to give the terminal silanide complex [(Me4 TACD)Sr(SiH3 )(thf)2 ][A], with release of H2 . Upon reaction with a weak Brønsted acid, CO2, and 1, 3, 5, 7‐cyclooctatetraene SiH4 was released. The reaction of a 1 : 2 mixture of cationic benzyl and neutral dibenzyl complex with phenylsilane gave the trinuclear silanide complex [(Me4 TACD)3 Sr3 (μ2 ‐H)3 (μ3 ‐SiH3 )2 ][A], while n OctSiH3 led to the trinuclear ( n ‐octyl)pentahydridosilicate complex [(Me4 TACD)3 Sr3 (μ2 ‐H)3 (μ3 ‐SiH5 n Oct)][A]. Abstract : A dinuclear strontium hexahydridosilicate complex has been isolated. It can be regarded as the adduct of two cationic strontium hydride fragments [(Me4 TACD)SrH(thf) x ] + with SiH4 .